Transforming Islamic Edupreneurship Values in Building an Education Ecosystem Based on Independence and Divine Blessings (International Journal of Education and Literature, 2025)
This study aims to analyze the transformation process of Islamic edupreneurship values in developing an educational ecosystem oriented toward independence and blessing (barakah) within Islamic schools. The low entrepreneurial and independent spirit among students remains a major challenge for Islamic educational institutions seeking to instill spiritually grounded entrepreneurship values. This research employed a qualitative descriptive approach through a case study at an Islamic elementary school. Data were collected through observation, interviews, and documentation. The results reveal that the internalization of Islamic edupreneurship values—such as amanah (trustworthiness), shidq (honesty), jiddiyyah (diligence), ibda‘ (creativity), and mas’uliyyah (responsibility)—successfully shifted students’ mindset from consumptive to productive orientation with a focus on barakah. The transformation occurred through curriculum integration, teacher modeling, socio-economic projects, and spiritual habituation. The Islamic edupreneurship-based ecosystem strengthened students’ character, microeconomic independence, and the culture of blessed work. This study recommends developing an Integrative Islamic Edupreneurship Curriculum Model to foster a competitive and morally upright generation.